Central compact osteoma of mandibular condyle. Issue 2 (10th February 2020) - Nilesh, Kumar; Vande, Aaditee; Reddy, Sridhar
Abstract : Osteomas are bone tumours arising from the cortical or medullary bones of craniofacial skeleton. Involvement of frontal bone and paranasal sinuses is more frequent than jaw bones. Jaw osteomas are slow growing benign lesions, which are usually asymptomatic or present as painless swelling. Those involving mandibular condyle are relatively rare and result in significant functional and aesthetic disturbances. This paper reports a case of solitary central compact osteoma of mandibular condyle in an adult Indian female patient. A comprehensive review of previously published reports is also presented.